Gavin Drewry, Louis Blom-Cooper, Charles Blake, The Court of Appeal - Charles James (The Windsor Yearbook of Access to Justice, 2008)
This study is an important contribution to access to justice scholarship and research. The subject is the English Court of Appeal as the authors found it in 2000–2001 responding to the deep and comprehensive agenda of change resulting from the “new public management” initiatives of the Tory and Labour governments in power during the 1980’s and 90’s. Although the study is concerned primarily with the present day operation and recent history of the Court of Appeal, significant events in the life of the court from its beginnings in the court restructuring legislation of the 1870’s are recounted and analyzed at appropriate junctures in the text. An important body of data was collected by the authors during 2000-2001 from which they describe and analyze the subjects, types and origins of cases, the throughput of applications and appeals and their outcomes, and in particular, the new requirement for permission to appeal.